2021
DOI: 10.3390/nano12010129
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heat Transfer for NePCM-Melting-Based Thermal Energy of Finned Heat Pipe

Abstract: Using phase change materials (PCMs) in energy storage systems provides various advantages such as energy storage at a nearly constant temperature and higher energy density. In this study, we aimed to conduct a numerical simulation for augmenting a PCM’s melting performance within multiple tubes, including branched fins. The suspension contained Al2O3/n-octadecane paraffin, and four cases were considered based on a number of heated fins. A numerical algorithm based on the finite element method (FEM) was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…The average Nusselt number passes through a local maximum and decreases gradually as the temperature of the PCM meted approaches that of the heated wall. Concerning the effect of adding nanoparticles, we notice from Figure 11B that the average Nusselt number diminished as the volume fraction of nanoparticles increased due to the decreases in the temperature gradients; this result is also inconsistent with those of Ahmed et al 35 …”
Section: Resultscontrasting
confidence: 94%
“…The average Nusselt number passes through a local maximum and decreases gradually as the temperature of the PCM meted approaches that of the heated wall. Concerning the effect of adding nanoparticles, we notice from Figure 11B that the average Nusselt number diminished as the volume fraction of nanoparticles increased due to the decreases in the temperature gradients; this result is also inconsistent with those of Ahmed et al 35 …”
Section: Resultscontrasting
confidence: 94%
“…Roughly speaking, in engineering and applied sciences, mathematical modeling, analysis, and techniques are widely used (see for instance [ 47 , 48 , 49 , 50 , 51 ]). With that has been said, an enthalpy–porosity analysis is a well-used approach for assessing unstable heat transfer situations, such as PCM phase transitions.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The use of NEPCM rather than only heat transfer fluid offers several benefits in many applications. NEPCM benefits from both heat transfer fluid and PCM characteristics [ 14 , 15 , 16 , 17 ]. For instance, it was recently shown that these could improve thermal storage characteristics and also for applications such as triple tube heat exchangers [ 18 ] or shell-and-tube heat exchangers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%